Unique architecture of thermophilic archaeal virus APBV1 and its genome packaging - Ptchelkine, D; Gillum, A; Mochizuki, T; Lucas-Staat, S; Liu, Y; Krupovic, M; Phillips, SEV; Prangishvili, D; Huiskonen, JT (Nature Publishing Group, 2017)
Archaeal viruses have evolved to infect hosts often thriving in extreme conditions such as high temperatures. However, there is a paucity of information on archaeal virion structures, genome packaging, and determinants of temperature resistance. The rod-shaped virus APBV1 (Aeropyrum pernix bacilliform virus 1) is among the most thermostable viruses known; it infects a hyperthermophile Aeropyrum pernix, which grows optimally at 90 °C. Here we report the structure of APBV1, determined by cryo-electron microscopy at near-atomic resolution. Tight packing of the major virion glycoprotein (VP1) is ensured by extended hydrophobic interfaces, and likely contributes to the extreme thermostability of the helical capsid. The double-stranded DNA is tightly packed in the capsid as a left-handed superhelix and held in place by the interactions with positively charged residues of VP1. The assembly is closed by specific capping structures at either end, which we propose to play a role in DNA packing and delivery.